Comprehensive characterisation of flexural mechanical properties and a new classification for porosity of 11 contemporary ion-leaching dental restorative materials. (September 2021) - Ruengrungsom, Chirayu; Burrow, Michael F.; Parashos, Peter; Palamara, Joseph E.A.
Abstract: The objectives of this study were to evaluate 4 aspects of ion-leaching restorative materials (ILMs): 4-point bending flexural strength (4 PB-FS) and relative mechanical properties; biaxial flexural strength (B-FS) in relation to 4 PB-FS; porosity; and surface morphology. Eleven ILMs were used for the 4-point bending test. Bar-shaped (n = 15) samples were fabricated, stored in distilled water for 7 days. Then 4 PB-FS and the other mechanical properties were determined. Five ILMs were selected for the B-FS test using disk specimens (n = 15). The correlation between 4 PB-FS and B-FS was addressed. After the 4 PB test, 5 randomised fragments from each material were used to make 0.5 mm-thick sections for light microscopy to investigate the degree of porosity using reflected and transmitted lights. Eight ILMs were selected for quantitative analysis of the fractional % pore volume (PV%) due to their relative pore prominence using ImageJ software. One-way ANOVA/Dunnett's T3 was used to test for significance. Resin-based ILMs (RB-ILMs) were ranked first (p < 0.05) for 4 PB-FS values (53.3–110.2 MPa) followed by resin-modified glass-ionomer cements (RMGICs; 30.9–44.3 MPa) and high-viscosity glass-ionomer cements (HVGICs; 12.9–19.6 MPa), respectively. 'Flexural modulus' (4 PB-E) and 'flexural toughness' (4 PB-T) of ILMs varied even though similar 4 PB-FS values were observed. There was a positive correlation (p < 0.001) between 4PB-FS and B-FS (R 2  = 0.992) with B-FS>4 PB-FS. There was no correlation between PV% and 4 PB-FS. In summary, material type played a major role in 4 PB-FS outcomes, whereas PV% seemed to have a minor effect when evaluating each material group of ILMs. Brittleness/ductility of ILMs was observed when determining 4 PB-E and 4 PB-T relative to 4 PB-FS. When selecting materials for posterior load-bearing dental restorations in high-caries risk patients, RB-ILMs or RMGICs would be more appropriate due to their superior flexural properties compared with recently introduced HVGICs. The decision for each situation will also be dependent on further evidence of the ion-leaching capacity. Highlights: Material type played a major role and porosity had a minor factor in influencing flexural strength (FS). Three resin-based ion leaching materials (RB-ILMs) displayed comparable FS; but flexural modulus and toughness were varied. Resin-modified glass-ionomer cements (RMGICs) exhibited the maximum porosity. RB-ILMs showed the highest FS followed by RMGICs and high-viscosity glass-ionomer cements (HVGICs).